2008
DOI: 10.1021/je800212c
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities and Densities of Halide Salts in Dimethylsulfoxide + Water from t = (25 to 45) °C

Abstract: The relative viscosities and densities for lithium bromide (LiBr) and sodium bromide (NaBr) were measured in dimethylsulfoxide (DMSO), water, and DMSO + water at temperatures from (25 to 45) °C. The estimated uncertainty of the measurements was ± 0.003 for relative viscosities and ± 0.0004 for densities. The data have been analyzed using the Jones−Dole equation. The Jones−Dole B-coefficients of these electrolytes were derived and the estimated uncertainty was ± 0.002. The values of the B-coefficients indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…The solvents in which negative B values are found , all have molecules capable of forming hydrogen bonding in three dimensions, and water is the prime example. The values of the B -coefficients of the reference salts from our previous papers , are presented in Table , which also coincide with the literature values for similar substances …”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The solvents in which negative B values are found , all have molecules capable of forming hydrogen bonding in three dimensions, and water is the prime example. The values of the B -coefficients of the reference salts from our previous papers , are presented in Table , which also coincide with the literature values for similar substances …”
Section: Resultssupporting
confidence: 86%
“…The measured physical parameters like densities (ρ o ) and viscosities (η ο ) for DMSO, water (H 2 O), and DMSO + H 2 O mixtures containing w 1 = (0, 0.2, 0.4, 0.5, 0.6, 0.7, and 1) % DMSO for temperatures of (25, 30, 35, 40, and 45) °C and the values of densities of pure water of this study are compared with the literature values and are reported in Table . The data used in this study for densities (ρ o ) and viscosities (η ο ) of the pure solvents H 2 O, DMSO, and DMSO + H 2 O mixtures are the same as used in our previous study …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of electrolyte solution is found to be helpful for various electrochemical and technical investigations [1][2][3][4]. Dimethyl sulphoxide is a polar aprotic solvent that has applicable properties in electrochemical systems [5,6]. Attentiveness of dimethylsulfoxide is due to the broad use of DMSO-H 2 O mixture as solvents and reaction media.…”
Section: Introductionmentioning
confidence: 99%